1996
DOI: 10.1007/bf00053902
|View full text |Cite
|
Sign up to set email alerts
|

Morphotypic plasticity in vitro and in nude mice of epithelial mouse mammary cells (NMuMG) displaying an epithelioid (e) or a fibroblastic (f) morphotype in culture

Abstract: Transition from an epithelioid (e-) to a fibroblastic (f-) morphotype marks invasiveness in clinical and experimental cancer. To understand better the factors influencing such transitions, we have subcloned and manipulated mouse mammary gland (NMuMG) cell cultures and compared the invasive phenotype of multiple subelones in vitro and in vivo. Cell lines with an e-morphotype expressed E-cadberin homogeneously and were not invasive in vitro. Cells with an f-morphotype were E-cadherin-negative and became fully in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…The heterogeneity in parental NMuMG cells might contribute to some of the inconsistencies we see in the literature concerning EMT in this cell line. Van den Broecke et al characterized subclones of NMuMG cells and reported that the epithelioid clones expressed E-cadherin homogenously and were not invasive whereas the fibroblastic clones were E-cadherin-negative and more invasive than the epithelioid clones (Van den Broecke et al, 1996). NMuMG/E9 cells and NMuMG/E11 cells are similar to the clones in this earlier report.…”
Section: Heterogeneity In Nmumg Cellssupporting
confidence: 75%
“…The heterogeneity in parental NMuMG cells might contribute to some of the inconsistencies we see in the literature concerning EMT in this cell line. Van den Broecke et al characterized subclones of NMuMG cells and reported that the epithelioid clones expressed E-cadherin homogenously and were not invasive whereas the fibroblastic clones were E-cadherin-negative and more invasive than the epithelioid clones (Van den Broecke et al, 1996). NMuMG/E9 cells and NMuMG/E11 cells are similar to the clones in this earlier report.…”
Section: Heterogeneity In Nmumg Cellssupporting
confidence: 75%
“…Both bTC and 4T1 cells stimulated migration of BPMECs (Figure 7g,j, arrowheads indicate endothelial cells; Figure 7l,m). The induction of migration appeared to be specific to tumor cells, as non-malignant NMuMg (Owens et al, 1974;Van den Broecke et al, 1996) cells did not induce BPMEC migration (Figure 7i,m). Addition of EphA2-Fc inhibited migration of BPMECs in response to both 4T1 and bTC (P50.01, Figure 7k,h,l,m), demonstrating that Eph A class receptor/ligand function is necessary for endothelial cell migration in response to tumor cells.…”
Section: Soluble Epha2-fc Inhibits 4t1 Tumor Cell-induced Angiogenesismentioning
confidence: 95%
“…We selected the 4T1 model due to the ability of transplanted 4T1 cells to rapidly and reproducibly generate mammary adenocarcinoma in syngeneic animals in vivo (Aslakson and Miller, 1992;Lin et al, 1998). Expression of ephrin-A1 and EphA2 in EMT6 cells was also analysed, as these tumor cells also produce malignant adenocarcinomas in vivo, though with a slower progression than 4T1 cells (Rockwell, 1977(Rockwell, , 1978(Rockwell, , 1981. As shown in Figure 3a, ephrin-A1 was barely detectable in normal primary mouse mammary epithelial cell (PMEC) lysates, but was expressed at high levels in 4T1 and EMT6 tumor cells.…”
Section: Soluble Epha2-fc Receptor Inhibits Rip-tag Tumorinduced Angimentioning
confidence: 99%
See 2 more Smart Citations